Need Needs Analysis for the Design of STEM-Based Electronic Worksheets to Facilitate Students’ Science Literacy in Thermodynamics - Nurhamiza Syazana; Dea Stivani Suherman; Hamdi; Renol Afrizon (Edusainstika, 2026)
Physics education requires the development of teaching materials capable of fostering students’ science literacy, particularly in the abstract and complex subject of thermodynamics. This study developed a STEM-based electronic student worksheet (E-LKPD) design using Liveworksheet to provide interactive and contextual learning at SMAN 2 Padang Panjang. The research method employed a Research and Development (R&D) approach, which included needs analysis, identification of student characteristics, and teacher interviews as initial data. Science literacy test results showed that the average student scores for the indicators “explaining phenomena scientifically” were 46%, “designing and evaluating investigations” were 51%, and “researching, evaluating, and using scientific information for decision-making” were 12%, all of which were classified as very low. An analysis of student characteristics revealed varying levels of interest and motivation to learn, while the available instructional materials consisted primarily of text-based worksheets and routine exercises that did not sufficiently support exploration, concept development, and active student engagement. These conditions highlight the need for instructional materials that are more adaptive, activity-rich, and contextual. The STEM-based electronic student worksheet design is viewed as a relevant and interactive teaching material capable of integrating conceptual, procedural, and reflective activities, as well as implicitly facilitating students’ comprehensive science literacy, helping them connect thermodynamics concepts to real-world phenomena, and enhancing a more meaningful learning experience.